2021
DOI: 10.1186/s40163-021-00157-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the COVID-19 pandemic on mental health calls for police service

Abstract: Drawing upon seven years of police calls for service data (2014–2020), this study examined the effect of the COVID-19 pandemic on calls involving persons with perceived mental illness (PwPMI) using a Bayesian Structural Time Series. The findings revealed that PwPMI calls did not increase immediately after the beginning of the pandemic in March 2020. Instead, a sustained increase in PwPMI calls was identified in August 2020 that later became statistically significant in October 2020. Ultimately, the analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
(53 reference statements)
0
7
1
Order By: Relevance
“…Similarity, unsurprisingly, was found to be much stronger at street segments. As such, while previous research has shown that PwPMI calls for service increased in Barrie during the COVID-19 pandemic relative to what would have been expected had the pandemic not occurred (Koziarski, 2021b), the findings here suggest that an overwhelming majority of these calls occurred in the very same place as in previous years. More research is certainly needed that not only conducts a more direct investigation into the effect of the pandemic on the spatial patterns of PwPMI calls for service, but the reasons as to why PwPMI calls appear to occur in the same place year-over-year, even during a pandemic.…”
Section: Research Implicationscontrasting
confidence: 62%
“…Similarity, unsurprisingly, was found to be much stronger at street segments. As such, while previous research has shown that PwPMI calls for service increased in Barrie during the COVID-19 pandemic relative to what would have been expected had the pandemic not occurred (Koziarski, 2021b), the findings here suggest that an overwhelming majority of these calls occurred in the very same place as in previous years. More research is certainly needed that not only conducts a more direct investigation into the effect of the pandemic on the spatial patterns of PwPMI calls for service, but the reasons as to why PwPMI calls appear to occur in the same place year-over-year, even during a pandemic.…”
Section: Research Implicationscontrasting
confidence: 62%
“…To assess whether the intervention significantly impacts the outcomes, BSTS then models the difference between the real outcome line with the invention and the estimated trend line without the invention (Brodersen et al, 2015 ). BSTS has been recently used in numerous studies to measure the impacts of the COVID-19 pandemic in various fields such as the public bicycle share system (Li et al, 2021 ), the stock market (Feng & Li, 2022 ) and mental health calls (Koziarski, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the geographic distribution of mental health-related calls was more evenly spread throughout the city during COVID-19 ( Lersch, 2020 ). Koziarski (2021) focused on CFS involving persons with a perceived mental illness in Barrie, Ontario, Canada. Results from the time series analyses indicated that COVID-19 had a delayed impact on mental health-related calls, with significant increases observed beginning in October 2020.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two areas of police work that have received attention in relation to the pandemic are calls for service (CFS) and proactive police activities. Several studies have examined changes to CFS patterns either for specific call types ( Demir & Park, 2021 ; Koziarski, 2021 ; Lersch, 2020 ; Miller, Segal, & Spencer, 2021 ; Nix & Richards, 2021 ) or more generally across multiple call types and/or jurisdictions ( Ashby, 2020 ; Dai, Xia, & Han, 2021 ; Mohler et al, 2020 ; White, Orosco, & Terpstra, 2022 ). Collectively, the results indicate that CFS trends have not been uniform, with variation observed between cities or call type (e.g., Ashby, 2020 ).…”
Section: Introductionmentioning
confidence: 99%